Me first, then the environment: young Millennials as green consumers - Naderi, Iman; Van Steenburg, Eric (My University, 2018)
Purpose This research aims to shed greater light on millennials' green behavior by examining four psychographic variables (selfless altruism, frugality, risk aversion, and time orientation) that may be relevant to millennials' motives to engage in environmental activities. Design/methodology/approach Data were collected from a sample of younger millennials (n = 276; age = 18 to 30) using a self-administered questionnaire. The data were then analyzed using structural equation modeling (SEM) technique. Findings Overall, the results of the study reveal that rational and self-oriented rather than emotional and others-oriented motives lead millennials to act pro-environmentally. Practical implications The findings of this study have implications for environmental advocates, policymakers and green marketers. For instance, the findings suggest that environmental regulators and lawmakers should continue their efforts to provide economic incentives to encourage pro-environmental purchases among millennials. Additionally, marketers of green products may pursue self-directed targeting strategies in promoting green products among millennials. Originality/value Millennials grasp the environmental consequences of their actions and have the education, motivation and social awareness to participate in the green movement. However, they have not truly begun to fully integrate their beliefs and actions. The present study is an initial attempt to address this issue by investigating various psychological factors that are relevant to the millennials' core behavioral motives.